Penerapan Pembelajaran Aktif, Inovatif, Efektif, Kreatif, Menyenangkan, dan Islami (PAIKEMI) - Nadia Nauli; Oktaviana Imroatun Cahyati; Gusmaneli Gusmaneli (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Active innovative effective creative fun and Islamic learning (Paikemi) is an approach to learning that integrates different elements to create an involving, inspiring and meaningful atmosphere in the learning process. This abstract will explore the application of Paikemi in the context of Islamic education. The application of Paikemi in Islamic learning aims to create a deep understanding of the principles of religion, ethics and morality taught in Islam. This is done through active, innovative, effective, creative, fun and Islamic methods. In the learning process, the teacher acts as a facilitator and motivator, while students are actively involved in exploring their knowledge and understanding.PAIKEMI learning in its application certainly has advantagas and disadvantages.